Effect of Calcium Chloride and Calcium Lactate on the Characteristics of Sweet Potato - Asman, Saliza; Mahadi, Suraya (Enhanced Knowledge in Sciences and Technology, 2021)
Sweet potatoes have gained popularity as a result of their adaptability to a wide variety of food production methods. However, due to the perishable nature of its properties, it was determined that sweet potato could be treated with calcium chloride and calcium lactate to circumvent this limitation. Hence, the effect of calcium salts on the sweet potato was investigated on the water activity, moisture content, colour measurement, texture analysis, sensory acceptance, and microbial growth. Three sweet potato samples were evaluated: untreated sweet potato (SP), sweet potato treated with calcium chloride (SP-CC), and sweet potato treated with calcium lactate (SP-CL). The samples of SP-CC and SP-CL had slightly lower water activity and moisture content mean values. Besides, both treated samples had a firmer texture than SP. Sensory analysis revealed that SP-CC and SP-CL possessed a stronger aroma, a saltier and bitterer flavour, but were less sweet than SP. No significant differences in colour measurement between the treated and control sweet potatoes were observed. Additionally, a microbial growth analysis revealed that the SP-CC and SP-CL had a longer shelf life of approximately 2-5 weeks than SP, which has a shelf life of only one week. As summarised, the calcium chloride and calcium lactate treatment affected the characteristics of sweet potatoes.